Applying the Concept of Fit to Water Governance Reforms in South Africa - Elke Herrfahrdt-Pähle (Ecology and Society, 2014)
The call for a spatial fit between institutional arrangements and the resource they manage is reflected in such water management paradigms as river basin management and in a number of international agreements (e.g., the European Union Water Framework Directive). Consequently, a number of countries are currently introducing river basin management, which, besides management along hydrological boundaries, has recently come to include such aspects of governance as stakeholder participation and policy integration. Beginning with a discussion of the goals and limitations of river basin management, this paper describes how the concept has been implemented in South Africa - a country that has been lauded for its state-of-the-art water legislation, but whose water administration is currently struggling to implement it. The example begins by showing the limitations of focusing on the dimension of spatial fit: a perfect spatial fit in basin management is almost impossible owing to the nature of the resource and to social and economic requirements. There are trade-offs between the identification of hydrological boundaries (which sometimes proves difficult) and "boundaries" of social organization, such as a feasible size for effective management, meaningful stakeholder participation, and financial viability. Furthermore, the improved spatial fit of the institutional arrangement and water resource boundaries causes problems of interplay by increasing the need for coordination and cooperation among water management organizations at different levels and on different scales. The example then considers the relevance of other dimensions of water management. It shows that, besides the focus on spatial fit, there is a need to recognize major defining features or boundaries to the problem other than hydrological boundaries, such as those imposed by water service infrastructure (functional fit) and impacts of climate change (dynamic fit), and a need to acknowledge the political and economic dimensions of water management.